Ion exchange resin for nickel recovery from wastewater and nickel sulfate recovery process

By adopting a three-layer structure ion exchange resin, the zeolite powder and resin composite materials in the toughening layer are used to solve the problem of resin crushing in the fluidized bed environment, the crushing strength and recycling efficiency of the resin are improved, and the wastewater is ensured Emissions meet standards.

CN117069899BActive Publication Date: 2025-02-07WENZHOU KERUI ENVIRONMENTAL RESOURCES UTILIZATION CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311079689.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-07
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

In the prior art, ion exchange resins are prone to breaking when used in a fluidized bed and other environment for a long time, resulting in a decrease in adsorption efficiency and affecting the recycling efficiency and wastewater discharge meet standards.

Method used

An ion exchange resin having a three-layer structure is used, including a pore-induced polystyrene resin core, a zeolite powder, a polystyrene resin and a bonding agent toughening layer, and a pore-induced shell layer. The toughening layer improves the structural strength and ion exchange ability of the resin through a composite material of zeolite powder and resin.

Benefits of technology

It significantly improves the crushing strength of the ion exchange resin, reduces the crushing loss of the resin in the fluidized bed, extends the service life of the resin, improves the recycling efficiency of nickel in wastewater, and ensures the compliance of wastewater discharge.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of nickel wastewater recovery, and discloses an ion exchange resin for nickel recovery from wastewater and a nickel sulfate recovery process. The ion exchange resin has an equivalent diameter of 2-3 mm and a core-shell structure, and includes a core, a toughening layer, and a shell layer from the inside to the outside. The core material is a porous polystyrene resin; the toughening layer is a composite of zeolite powder, polystyrene resin, and a binder. The raw materials of the toughening layer have a mass ratio of zeolite powder, polystyrene resin, and binder of (22-27):100:(10-14); the shell layer is a porous polystyrene resin. The toughening layer improves the strength of the ion exchange resin, redistributes ions when the concentration of the treatment solution fluctuates, and blocks ion penetration when the high-concentration liquid contacts due to process errors, so that the ion exchange resin can operate stably for a long time and with a high exchange capacity in a working environment such as a fluidized bed where the concentration of liquid ions fluctuates frequently and the fluctuation range is large.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nickel wastewater recovery, and in particular to an ion exchange resin for recovering nickel from wastewater and a nickel sulfate recovery process. Background Art

[0002] Because the nickel plating process requires a certain amount of dosage, the process wastewater from electroplating nickel and chemical nickel plating generally contains a relatively high concentration of nickel sulfate. This wastewater cannot be discharged directly and the nickel sulfate must be removed or recovered from the wastewater.

[0003] At present, the process of recovering nickel sulfate from wastewater is conducive to the adsorption of nickel in the wastewater by cation exchange resin, and then the nickel sulfate is concentrated and recovered by subsequent desorption. For example, patent CN111233209A-A nickel-containing wastewater reuse device and method discloses a method for recovering nickel ions in water by using a resin adsorption system after a membrane filtration system. The resin adsorption system includes a plurality of groups of resin adsorption tanks connected in series, and a weak acid cation exchange resin is arranged in the resin adsorption tank. The wastewater enters the tank from the bottom of the first resin adsorption tank, and after contacting with the resin in the first resin adsorption tank, it enters from the bottom of the second resin adsorption tank, thereby passing through a plurality of resin adsorption tanks connected in series one by one, and the nickel ion concentration in the wastewater is greatly reduced by the resin.

[0004] In further actual production, the following considerations are made for the resin in the resin adsorption tank: in order to increase the contact area and contact time between the wastewater and the resin, a fluidized bed design is adopted for the resin adsorption tank so that the resin is suspended and dispersed by the flow of wastewater; in order to avoid the loss of resin when the wastewater flows out of the next resin adsorption tank or outflow equipment, on the other hand, since the nickel ion concentration of the wastewater gradually decreases when passing through the resin adsorption tank one by one, in order to control the saturation of the resin in the resin adsorption tank for regeneration and desorption, a limit plate for limiting the suspension rise of the resin or a baffle with an uneven surface installed at each liquid outlet of the resin adsorption tank will be installed.

[0005] Therefore, although the resin is highly efficient, not easy to flow out, and not easy to flow between the resin adsorption tanks of each level, the resins will collide with each other as the wastewater flow rate fluctuates, and the resins will collide with the limit plates / baffles, and the resins are easy to break. There are still some relatively considerable resins that are damaged and easily inactivated, which reduces the adsorption efficiency of nickel ions in wastewater after long-term work, affecting the recovery efficiency and whether the wastewater discharge meets the standards. Summary of the invention

[0006] In order to reduce the breakage loss during the long-term operation of the resin fluidized bed process, an ion exchange resin for recovering nickel from wastewater and a nickel sulfate recovery process are provided.

[0007] The first invention objective of the present invention is achieved through the following technical solutions:

[0008] An ion exchange resin for recovering nickel from wastewater,

[0009] The resin equivalent diameter is 2~3mm, with a core-shell structure, including a core, a toughening layer, and a shell layer from the inside to the outside.

[0010] The core material is a porous polystyrene resin;

[0011] The toughening layer is composed of zeolite powder, polystyrene resin and binder, and the mass ratio of zeolite powder, polystyrene resin and binder in the raw materials of the toughening layer is (22-27):100:(10-14);

[0012] The shell layer is a porous polystyrene resin.

[0013] By adopting the above technical solution, the ion exchange resin of the present application has a three-layer structure, wherein the toughening layer is located between the core and the shell layer, and is composited with zeolite powder, polystyrene resin, and a binder, and has an ion permeation channel, so that the ions of the shell layer can pass through and be absorbed by the core and the toughening layer;

[0014] At the same time, the toughening layer has good structural strength, and the toughening layer protects the core layer, thereby significantly improving the overall crushing strength of the ion exchange resin, reducing the crushing loss of the ion exchange resin when working in fluidized beds, bubble towers and other similar units, thereby increasing the exchange capacity of the ion exchange resin for long-term use after filling, improving the recovery efficiency and ensuring that the wastewater discharge meets the standards;

[0015] In addition, the volume of ion exchange resin will expand after absorbing ions. If the local concentration is too high or a large amount of high-concentration ions are absorbed in a short time, the ion exchange resin will expand too fast locally, and the internal stress will be concentrated and cracked. In fluidized bed, bubble tower and other units, concentration fluctuations are common and the local concentration fluctuation range is large.

[0016] The ion channels of the zeolite powder in the toughening layer of the present application migrate slower than the ion channels of the resin.

[0017] When the concentration of ions migrating inward from the shell layer is low, they can quickly enter the core area through the migration channel of the resin in the toughening layer, ensuring that the ion migration speed between the layers of the ion exchange resin is fast when the concentration is low;

[0018] When the shell layer is affected by the external liquid ion concentration and the local concentration is high, the toughening layer blocks the rapid penetration of the ions with too high concentration, and the high concentration ions diffuse to the surrounding in the shell layer, diluting the high concentration ions in the local shell layer. The toughening layer mixed with zeolite powder can make the toughening layer itself and the transition zone between the toughening layer and the shell layer resist the stress concentration caused by the excessive local ion concentration, play a role in ion concentration redistribution and avoid the cracking of ion exchange resin caused by local instantaneous fluctuations in liquid concentration.

[0019] When the ion concentration in the external liquid is uniform and too high for a long time (usually caused by process operation errors), the toughening layer completely limits the entry of high-concentration ions in the shell layer, thereby protecting the core and reducing the loss of ion exchange resin due to process operation errors.

[0020] In summary, the present application improves the strength of the ion exchange resin through the toughening layer, and blocks ion redistribution when the concentration of the processing solution fluctuates, and ion penetration when it comes into contact with high-concentration liquids caused by process errors, so that the ion exchange tree can operate stably for a long time and with a high exchange capacity in working environments such as fluidized beds where fluctuations in liquid ion concentration are common and have a large fluctuation range.

[0021] Optionally, the thickness of the toughening layer is 9-11% of the resin equivalent diameter, and the particle size of the zeolite powder is 0.32-0.44% of the resin equivalent diameter.

[0022] By adopting the above technical solution, as the proportion of the toughening layer thickness increases, the crushing strength of the ion exchange resin increases, but after the toughening layer thickness increases to a certain threshold, the exchange saturation rate of the ion exchange resin decreases significantly. This is because the toughening layer thickness is too large, the outer thickening layer has completed the path redistribution of ion exchange, and the evenly distributed ions still need to move in the inner toughening layer with a slower migration speed, resulting in a decrease in the exchange saturation rate;

[0023] When the thickness of the toughening layer is in the above ratio, the ion exchange resin reaches the optimal solution between the crushing strength and the exchange rate, and the crushing strength and the difficulty of preparation reach the optimal solution when the zeolite powder particle size is 0.32~0.44% of the resin equivalent diameter.

[0024] Optionally, the zeolite powder is modified by a silane coupling agent, and the modification method is as follows:

[0025] placing zeolite powder in an organic solution and dispersing it ultrasonically to obtain a zeolite powder suspension;

[0026] Add silane coupling agent to the zeolite powder suspension, stir evenly, centrifuge and dry to obtain modified zeolite powder.

[0027] By adopting the above technical scheme, the compatibility of zeolite powder and organic phase is improved, making the zeolite powder suspension easier to prepare, and the suspension time of zeolite powder is longer and the suspension state is more stable, reducing the difficulty of toughening layer molding and making the zeolite powder more evenly dispersed in the toughening layer, and the toughening layer has better reinforcement effect, ion redistribution and high concentration resistance on ion exchange resin.

[0028] Optional: The particle size of the zeolite powder is 9~11μm.

[0029] By adopting the above technical solution, the zeolite powder suspension is easier to prepare while ensuring the strengthening effect of the toughening layer, and the zeolite powder in the prepared zeolite powder suspension has a longer suspension time and a more stable suspension state.

[0030] Optionally, the mass ratio of the silane coupling agent to the zeolite powder is (0.05-0.08):1.

[0031] By adopting the above technical solution, the silane coupling agent improves the compatibility of zeolite powder with the organic phase and affects the ion channel in the zeolite powder. As the amount of silane coupling agent used relative to zeolite powder increases, more silane is grafted on the surface of the zeolite powder. After reaching a certain threshold, the ion channel on the surface of the zeolite powder will be affected by the steric hindrance of the grafted silane, and the ion passage speed will decrease.

[0032] When the drop is small, the toughening layer has a synergistic effect on the resistance of high-concentration ions, but the range is very small. When the drop is large, it will affect the entry of ions into the core through the ion channel of zeolite powder during normal operation, affecting the overall exchange rate of the ion exchange resin.

[0033] The zeolite powder obtained by the above-mentioned modification has good compatibility with the organic phase, and the silane coupling agent has little effect on the ion migration channel in the zeolite powder, so the effect is better.

[0034] Optionally, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0035] By adopting the above technical solution, the silane coupling agent has a better effect than other silane coupling agents.

[0036] Optional: The binder is polymethacrylic acid.

[0037] By adopting the above technical solution, when the binder is polymethacrylic acid, the zeolite powder has good binding property with the organic phase and high crushing strength.

[0038] The second invention objective of the present invention is achieved through the following technical solutions:

[0039] A process for recovering nickel from wastewater uses the above-mentioned ion exchange resin for recovering nickel from wastewater.

[0040] By adopting the above technical scheme, the wastewater nickel recovery process of the present application can recover nickel from wastewater in a long-term and stable manner, and has a good recovery efficiency for wastewater with large concentration fluctuations.

[0041] In summary, this application has at least the following beneficial effects:

[0042] The present application improves the strength of the ion exchange resin through a toughening layer, and blocks ion redistribution when the concentration of the processing solution fluctuates, and ion penetration when in contact with high-concentration liquids caused by process errors, so that the ion exchange tree can operate stably for a long time and with a high exchange capacity in a working environment such as a fluidized bed where liquid ion concentration fluctuations are common and the fluctuation range is large. Implementation

[0043] Styrene and divinylbenzene are commercially available pharmaceutical products;

[0044] Zeolite powder is a customized particle size product produced by Lingshou County Fengju Mineral Products Processing Plant;

[0045] The binder includes methacrylic acid and acrylic acid, which are commercially available products.

[0046] Silane coupling agents include n-octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane, which are commercially available products.

[0047] The organic solvent may be any solvent that does not react with the zeolite powder, is volatile, and can dissolve the silane coupling agent. Acetone is used as the organic solvent below.

[0048] A modified zeolite powder is prepared as follows:

[0049] Add zeolite powder with a particle size of 11±1 μm into acetone at a ratio of 200 g / L, stir, and use ultrasonic vibration to mix evenly to obtain a zeolite powder suspension;

[0050] Add silane coupling agent γ-glycidyloxypropyltrimethoxysilane to the zeolite powder suspension, the mass ratio of γ-glycidyloxypropyltrimethoxysilane to zeolite powder is 0.07:1, continue stirring at 100 r / min for 5 minutes, and then filter, dry and sieve to obtain modified zeolite powder with a particle size of 10±1 μm.

[0051] A modified zeolite powder, which is different from that in Preparation Example 1 in that the particle size of the zeolite powder used is 13±1 μm.

[0052] A modified zeolite powder, which is different from Preparation Example 1 in that the silane coupling agent used is n-octyltrimethoxysilane.

[0053] A modified zeolite powder is different from Preparation Example 1 in that the silane coupling agent used is anilinemethyltriethoxysilane.

[0054] A modified zeolite powder, which is different from Preparation Example 1 in that the mass ratio of silane coupling agent γ-glycidyloxypropyltrimethoxysilane to zeolite powder is 0.02:1.

[0055] A modified zeolite powder, which is different from Preparation Example 1 in that the mass ratio of silane coupling agent γ-glycidyloxypropyltrimethoxysilane to zeolite powder is 0.05:1.

[0056] A modified zeolite powder, which is different from Preparation Example 1 in that the mass ratio of silane coupling agent γ-glycidyloxypropyltrimethoxysilane to zeolite powder is 0.08:1.

[0057] A modified zeolite powder, which is different from Preparation Example 1 in that the mass ratio of silane coupling agent γ-glycidyloxypropyltrimethoxysilane to zeolite powder is 0.1:1. Example

[0058] An ion exchange resin for nickel recovery from wastewater has a three-layer core-shell structure, which includes a central core, a middle toughening layer, and an outer shell layer from the inside to the outside. The equivalent particle size of the ion exchange resin for nickel recovery from wastewater is 3 mm, and the screening deviation is ±0.1 mm.

[0059] The equivalent diameter of the core accounts for 60±1% of the equivalent particle size of the ion exchange resin, that is, the equivalent particle size is 1.8±0.03 mm.

[0060] The toughening layer is obtained by coating and polymerizing zeolite powder, polystyrene resin and binder methacrylic acid on the outer side of the core. The thickness of the toughening layer is 10±1% of the resin equivalent particle size, that is, the thickness is 0.3±0.03mm.

[0061] The shell layer is polymerized with polystyrene resin outside the toughening layer, and the thickness is 10±1% of the resin equivalent particle size, that is, the thickness is 0.3±0.03mm.

[0062] The preparation method of the ion exchange resin for recovering nickel from wastewater is as follows:

[0063] S1: 60 g of styrene monomer, 55 g of divinylbenzene, 17 g of liquid paraffin, and 0.4 g of benzoyl peroxide as a core initiator are mixed evenly to obtain an oil liquid;

[0064] 400 g of water, 2.3 g of polyethylene oxide ethoxylated stearyl alcohol as a core emulsifier, and 0.1 g of p-diphenol as an inhibitor were mixed evenly to obtain a reaction water phase;

[0065] The reaction water phase was stirred at a speed of 100 r / min and heated to 50°C, and the oil phase was added dropwise. The oil phase was added dropwise for 30 min, i.e., the addition was completed within 30 min. At the same time, the temperature was raised to 70°C at a speed of 1°C / min. After the temperature was raised to 70°C, the temperature was kept warm until the oil phase was added dropwise, thereby obtaining a primary polymer material.

[0066] S2: After the addition of S1 is completed, the secondary polymerization raw material liquid is immediately added, and the secondary polymerization raw material liquid is obtained by mixing 25g of zeolite powder, 67g of styrene monomer, 33g of divinylbenzene, 300g of water, 1.2g of polyethylene oxide ethoxylated stearyl alcohol as a toughening layer emulsifier, 0.4g of benzoyl peroxide as a toughening layer initiator, and 12g of methacrylic acid as a binder. After the addition, the material is heated to 80°C at a speed of 3°C / min, and reacted for 30min to obtain a secondary polymer material;

[0067] S3: 60g of styrene monomer, 32g of divinylbenzene, 200g of water, 14g of liquid paraffin, 1.4g of polyethylene oxide ethoxylated stearyl alcohol as a shell emulsifier, and 0.22g of benzoyl peroxide as a shell initiator were mixed uniformly according to the mass ratio to obtain a tertiary polymerization raw material solution, the secondary polymerization material was cooled to 60°C, the tertiary polymerization raw material solution was added to react for 20min, 0.04g of p-diphenol as an inhibitor was added, the reaction was continued for 10min, and the ball material was filtered;

[0068] S4: adding the ball material to acetone for repeated extraction to remove the liquid paraffin, filtering, drying, and screening the particle size to obtain a porous ball material;

[0069] S5: The porogenic ball material is completely immersed in a saturated sulfur trioxide dichloroethane solution, stirred and reacted at 100°C for 15 hours, cooled to room temperature after the reaction, rinsed with deionized water until neutral, and filtered to obtain the ion exchange resin.

[0070] During the research process of this embodiment, the materials obtained in each step were tested to measure the core equivalent diameter, toughening layer thickness, shell thickness, and the sizes and proportions of the core, toughening layer, and shell layer mentioned above were obtained.

[0071] The zeolite powder in this embodiment is unmodified zeolite powder, and the particle size is 3±1 μm.

[0072] The invention discloses an ion exchange resin, which is obtained by polymerizing and vulcanizing a polystyrene resin.

[0073] The preparation method is as follows:

[0074] S1: 60 g of styrene monomer, 55 g of divinylbenzene, 17 g of liquid paraffin, 0.4 g of core initiator benzoyl peroxide, and 12 g of binder methacrylic acid were mixed uniformly to obtain an oil liquid;

[0075] 400 g of water, 2.3 g of polyethylene oxide ethoxylated stearyl alcohol as a core emulsifier, and 0.1 g of p-diphenol as an inhibitor were mixed evenly to obtain a reaction water phase;

[0076] The reaction water phase was stirred at a speed of 100 r / min and heated to 50°C, and the oil phase was added dropwise. The oil phase was added dropwise for 30 minutes, that is, the addition was completed within 30 minutes. At the same time, the temperature was raised to 70°C at a speed of 1°C / min. After the temperature was raised to 70°C, it was kept warm until the oil phase was added dropwise, thereby obtaining a primary polymer material;

[0077] S2: After the addition of S1 is completed, the secondary polymerization raw material liquid is immediately added, and the secondary polymerization raw material liquid is obtained by uniformly mixing 80.4g of styrene monomer, 39.6g of divinylbenzene, 300g of water, 1.4g of toughening layer emulsifier, and 0.42g of toughening layer initiator. After adding, the material is heated to 80°C at a speed of 3°C / min, and reacted for 30min to obtain a secondary polymer material;

[0078] S3: 60g of styrene monomer, 32g of divinylbenzene, 200g of water, 14g of liquid paraffin, 1.4g of shell emulsifier and 0.22g of shell initiator were mixed uniformly according to the mass ratio to obtain a tertiary polymerization raw material liquid, the secondary polymerization material was cooled to 60°C, the tertiary polymerization raw material liquid was added to react for 20min, 0.04g of polymerization inhibitor p-diphenol was added, the reaction was continued for 10min, and the ball material was filtered;

[0079] S4: adding the ball material to acetone for repeated extraction to remove the liquid paraffin, filtering, drying, and screening the particle size to obtain a porous ball material;

[0080] S5: The porogenic ball material is completely immersed in a saturated sulfur trioxide dichloroethane solution, stirred and reacted at 100°C for 15 hours, cooled to room temperature after the reaction, rinsed with deionized water until neutral, and filtered to obtain the ion exchange resin.

[0081] In this example, the zeolite powder is unmodified zeolite powder, and the particle size is 3±1 μm.

[0082] The equivalent particle size of the obtained ion exchange resin is 3±0.1 mm, wherein the equivalent diameter of the core accounts for 60±1% of the equivalent particle size of the ion exchange resin, that is, the equivalent particle size is 1.8±0.03 mm.

[0083] The preparation method of the ion exchange resin for recovering nickel from wastewater is as follows:

[0084] S1: 120 g of styrene monomer, 82 g of divinylbenzene, 31 g of liquid paraffin, and 0.4 g of benzoyl peroxide as a core initiator are mixed evenly to obtain an oil liquid;

[0085] Mix 600 g of water, 2.7 g of polyethylene oxide ethoxylated stearyl alcohol as a core emulsifier, and 0.2 g of p-diphenol as an inhibitor to obtain a reaction water phase;

[0086] The reaction water phase was stirred at a speed of 100 r / min and heated to 50°C, and the oil phase was added dropwise. The oil phase was added dropwise for 30 minutes, that is, the addition was completed within 30 minutes. At the same time, the temperature was raised to 70°C at a speed of 1°C / min. After the temperature was raised to 70°C, it was kept warm until the oil phase was added dropwise, thereby obtaining a primary polymer material;

[0087] S2: After the addition of S1 is completed, the secondary polymerization raw material liquid is immediately added, which is obtained by mixing 25g of zeolite powder, 67g of styrene monomer, 33g of divinylbenzene, 300g of water, 1.2g of toughening layer emulsifier, 0.4g of toughening layer initiator, and 12g of binder methacrylic acid. After adding, the material is heated to 80°C at a speed of 3°C / min, reacted for 30min, and a secondary polymer material is obtained, which is filtered to obtain a ball material;

[0088] S3: adding the ball material to acetone for repeated extraction to remove the liquid paraffin, then filtering, drying, and screening the particle size to obtain a porous ball material;

[0089] S4: The porogenic ball material is completely immersed in a saturated sulfur trioxide dichloroethane solution, stirred and reacted at 100°C for 15 hours, cooled to room temperature after the reaction, rinsed with deionized water until neutral, and filtered to obtain the ion exchange resin.

[0090] In this example, the zeolite powder is unmodified zeolite powder, and the particle size is 3±1 μm.

[0091] The obtained ion exchange resin equivalent particle size is 3±0.1 mm, and the thickness of the toughening layer is 10±1% of the resin equivalent particle size, that is, the thickness is 0.3±0.03 mm.

[0092] An ion exchange resin, the preparation method is as follows:

[0093] S1: 25 g of zeolite powder, 60 g of styrene monomer, 55 g of divinylbenzene, 17 g of liquid paraffin, and 0.4 g of a core initiator benzoyl peroxide were mixed uniformly to obtain an oil liquid;

[0094] 400 g of water, 2.3 g of polyethylene oxide ethoxylated stearyl alcohol as a core emulsifier, and 0.1 g of p-diphenol as an inhibitor were mixed evenly to obtain a reaction water phase;

[0095] The reaction water phase was stirred at a speed of 100 r / min and heated to 50°C, and the oil phase was added dropwise. The oil phase was added dropwise for 30 min, i.e., the addition was completed within 30 min. At the same time, the temperature was raised to 70°C at a speed of 1°C / min. After the temperature was raised to 70°C, the temperature was kept warm until the oil phase was added dropwise, thereby obtaining a primary polymer material.

[0096] S2: After the addition of S1 is completed, the secondary polymerization raw material liquid is immediately added, and the secondary polymerization raw material liquid is obtained by uniformly mixing 67g of styrene monomer, 33g of divinylbenzene, 300g of water, 1.2g of polyethylene oxide ethoxylated stearyl alcohol as a toughening layer emulsifier, 0.4g of benzoyl peroxide as a toughening layer initiator, and 12g of methacrylic acid as a binder. After the addition, the material is heated to 80°C at a speed of 3°C / min, and reacted for 30min to obtain a secondary polymer material;

[0097] S3: 60g of styrene monomer, 32g of divinylbenzene, 200g of water, 14g of liquid paraffin, 1.4g of polyethylene oxide ethoxylated stearyl alcohol as a shell emulsifier, and 0.22g of benzoyl peroxide as a shell initiator were mixed uniformly according to the mass ratio to obtain a tertiary polymerization raw material solution, the secondary polymerization material was cooled to 60°C, the tertiary polymerization raw material solution was added to react for 20min, 0.04g of p-diphenol as an inhibitor was added, the reaction was continued for 10min, and the ball material was filtered;

[0098] S4: adding the ball material to acetone for repeated extraction to remove the liquid paraffin, filtering, drying, and screening the particle size to obtain a porous ball material;

[0099] S5: The porogenic ball material is completely immersed in a saturated sulfur trioxide dichloroethane solution, stirred and reacted at 100°C for 15 hours, cooled to room temperature after the reaction, rinsed with deionized water until neutral, and filtered to obtain the ion exchange resin.

[0100] In this example, the zeolite powder is unmodified zeolite powder, and the particle size is 3±1 μm.

[0101] The equivalent diameter of the core accounts for 60±1% of the equivalent particle size of the ion exchange resin, that is, the equivalent particle size is 1.8±0.03 mm.

[0102] The crushing strength, saturated exchange capacity and exchange rate of the ion exchange resins obtained in Example 1 and Comparative Examples 1 to 3 were tested.

[0103] The exchange rate = 50% saturated exchange capacity / time to reach 50% saturated exchange capacity.

[0104] The test results are described below.

[0105] Table 1. Test results of Example 1 and Comparative Examples 1 to 3

[0106] Crushing strength N / particle Saturated exchange capacity mmol / g Exchange rate mmol / (g·h) Example 1 9.1 2.59 1.05 Comparative Example 1 8 2.22 1.17 Comparative Example 2 8.6 2.1 1.12 Comparative Example 3 7.8 2 1.15

[0107] The ion exchange resin of the present application has a three-layer core-shell structure, in which the middle layer is a toughening layer dispersed with zeolite powder, and the zeolite powder and resin material of the toughening layer both have ion permeation channels, so that the ions of the shell layer can pass through and be absorbed by the core and the toughening layer; at the same time, the toughening layer has good structural strength, and the toughening layer protects the core layer, thereby significantly improving the overall crushing strength of the ion exchange resin, reducing the crushing loss of the ion exchange resin when working in fluidized beds, bubble towers and other similar units, thereby increasing the exchange capacity of the ion exchange resin for long-term use after filling, improving the recovery efficiency, and ensuring that the wastewater discharge meets the standards.

[0108] Combining Example 1 and Comparative Example 1, the ion exchange resin of Example 1 has a three-layer core-shell structure and the middle layer is a toughening layer. Compared with Comparative Example 1 which is obtained by three-layer polymerization but the polymerization raw materials are all polystyrene resin, the crushing strength of Example 1 of the present application is significantly higher than that of Comparative Example 1.

[0109] On the other hand, the toughening layer in the ion exchange resin of the present application also has an ion redistribution effect. The ion channels of the zeolite powder in the toughening layer migrate slower than the ion channels of the resin. When the shell layer is affected by the external liquid ion concentration and the local concentration is high, the toughening layer prevents the excessively high concentration of ions from quickly penetrating. The high concentration of ions diffuses to the surroundings in the shell layer, diluting the high concentration of ions in the local shell layer, so that the ion exchange resin as a whole can more fully absorb and exchange with the ions in the liquid, making the saturated exchange capacity of the ion exchange resin larger and closer to the theoretical maximum exchange capacity, thereby making the ion saturated exchange capacity of Example 1 greater than that of Comparative Example 1.

[0110] In the present application, the toughening layer is located between the core and the shell layer, and the ion redistribution effect of the toughening layer can be achieved only when the shell layer with faster ion absorption and ion passing speed is outside.

[0111] As shown in Comparative Example 2, the toughening layer is the outermost layer and directly contacts the ionic liquid. The liquid directly enters the core layer through the holes in the resin part of the toughening layer, and only a small amount passes through the ion channel of the zeolite powder. In the case where the ion redistribution effect of the toughening layer fails, the ion saturation capacity of Comparative Example 2 is reduced compared with Comparative Example 1 due to the addition of zeolite powder.

[0112] In addition, from the comparison between Comparative Example 2 and Example 1, it can be seen that without the softer shell layer for buffering protection, the toughening layer on the outside has a weaker effect on the crushing strength of the ion exchange resin.

[0113] The three-layer core-shell structure of the present application ensures that the hardness of the ion resin shell and the core is softer than the toughening layer. While the toughening layer improves the strength, the shell protects the toughening layer from the outside as described above, and the core cushions the impact of the ion exchange resin from the inside, avoiding local breakage and cracking that may cause overall cracking.

[0114] Comparative Example 3 is a two-layer core-shell structure, zeolite powder is added to the core, and the hardness of the ion exchange resin center is large. Combining Example 1, Comparative Example 1 and Comparative Example 3, it can be seen that the crushing strength of Comparative Example 3 is not only weaker than that of Example 1, but also weaker than that of Comparative Example 1. This is because the shell layer is pressed by the inner and outer sides when it is squeezed, and the unloading force is insufficient, which is easy to crack locally, and finally causes overall cracking. In the sample after the test of Comparative Example 3, it is also observed that most of the resin particles have surface peeling.

[0115] In summary, the present application improves the strength of the ion exchange resin through the toughening layer, so that the ion exchange resin can operate stably for a long time and with a high exchange capacity in the fluidized bed.

[0116] The present application also tests the liquid ion concentration fluctuation of the resins of Example 1 and Comparative Examples 1 to 3, and selects nickel sulfate solution as the test liquid, and the test liquids are test liquid 1 (nickel ion concentration is 50 ppm) and test liquid 2 (nickel ion concentration is 300 ppm).

[0117] Test 1: 100g of ion resin is fixedly filled into a container, and the flow cross section is a circle with a diameter of 5cm. Test liquid 1 is passed at 1.5L / min. After 5min, test liquid 2 is switched, and after another 5min, test liquid 1 is switched. Repeat the switching until the total exchange time is 1h. The flow time of test liquid 1 and test liquid 2 is 30min. The resin is desorbed and the residual nickel content in the resin is measured to obtain the total exchange capacity of the ion exchange resin within 1h, which is used to calculate

[0118] Test 2: Immerse the ion exchange resin in test solution 2 at a ratio of 100 g / L for 10 minutes, then take it out and conduct a crushing strength test.

[0119] The test results of Test 1 and Test 2 are as follows.

[0120] Table 2. Test 1 and Test 2 results of Example 1 and Comparative Examples 1 to 3

[0121] For the ion exchange resin of this application:

[0122] When the concentration is stable, the concentration of ions migrating inward from each area of ​​the shell is low, and the ions can quickly enter the core area through the migration channel of the resin in the toughening layer, ensuring the ion migration speed between the layers of the ion exchange resin when the concentration is low; when the concentration fluctuates, the shell is affected by the external liquid ion concentration and the local concentration is high. The toughening layer hinders the rapid penetration of ions with excessively high concentrations. The high-concentration ions diffuse to the surroundings in the shell, diluting the high-concentration ions in the local area of ​​the shell. The acting ions under ion redistribution quickly penetrate, accelerating the exchange rate of the ion exchange resin.

[0123] Therefore, combining the exchange rate in Table 1 and the test 1 result in Table 2, it can be seen that the exchange rates of Example 1 and Comparative Examples 1 to 3 changed under fluctuating concentration conditions, and the absorption rates of the ion exchange resins decreased under fluctuating concentrations, but the decrease in Example 1 of the present application was significantly weaker than that of Comparative Examples 1 to 3, and the exchange amount of Example 1 of the present application in 1h under ion concentration fluctuations was greater than that of Comparative Examples 1 to 3, that is, the ion exchange rate of the ion exchange resin of the present application under ion concentration fluctuations was greater than that of the existing ion exchange resin.

[0124] In addition, combining the crushing strength in Table 1 and the test 2 results in Table 2, it can be seen that the crushing strength advantage of the ion exchange resin in Example 1 after contact with high-concentration ionic liquid is more obvious than that of Comparative Examples 1 to 3, which is also achieved by the toughening layer in the three-layer structure of the present application.

[0125] Mixing zeolite powder into the toughening layer can make the toughening layer itself and the transition zone between the toughening layer and the shell layer resist the stress concentration caused by excessive local ion concentration, avoid the cracking of ion exchange resin caused by local instantaneous fluctuations in liquid concentration, and when the ion concentration in the external liquid is uniform and too high for a long time (generally caused by process operation errors), the toughening layer comprehensively restricts the entry of high-concentration ions in the shell layer, thereby protecting the core and reducing the loss of ion exchange resin due to process operation errors. Example

[0126] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that zeolite powder with a particle size of 6±0.1 μm is used. Example

[0127] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that zeolite powder with a particle size of 10±0.1 μm is used. Example

[0128] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that zeolite powder with a particle size of 13±0.1 μm is used. Example

[0129] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that zeolite powder with a particle size of 18±0.1 μm is used.

[0130] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that the modified zeolite powder is prepared using the preparation example, and the specific source is as follows.

[0131] Table 3. Sources of modified zeolite powders in Examples 6 to 13 Example

[0132] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that the secondary polymerization raw material liquid in S2 is 18g of zeolite powder, 48.2g of styrene monomer, 23.8g of divinylbenzene, 246g of water, 0.86g of toughening layer emulsifier, and 0.29g of toughening layer initiator.

[0133] The thickness of the toughening layer sampled and tested was 0.225±0.03mm, accounting for 7.5±0.1% of the resin equivalent particle size. Example

[0134] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that the secondary polymerization raw material liquid in S2 is 22g of zeolite powder, 59g of styrene monomer, 29g of divinylbenzene, 264g of water, 1.06g of toughening layer emulsifier, and 0.35g of toughening layer initiator.

[0135] The thickness of the toughening layer sampled and tested was 0.27±0.03mm, accounting for 9±1% of the resin equivalent particle size. Example

[0136] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that the secondary polymerization raw material liquid in S2 is 30g of zeolite powder, 80.4g of styrene monomer, 39.6g of divinylbenzene, 360g of water, 1.44g of toughening layer emulsifier, and 0.48g of toughening layer initiator.

[0137] The thickness of the toughening layer sampled and tested was 0.33±0.03mm, accounting for 9±1% of the resin equivalent particle size. Example

[0138] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that the secondary polymerization raw material liquid in S2 is 20g of zeolite powder, 67g of styrene monomer, 33g of divinylbenzene, 300g of water, 1.2g of toughening layer emulsifier, and 0.4g of toughening layer initiator. Example

[0139] An ion exchange resin for recovering nickel from wastewater is similar to Example 1, except that the secondary polymerization raw material liquid in S2 is 30g of zeolite powder, 67g of styrene monomer, 33g of divinylbenzene, 300g of water, 1.2g of toughening layer emulsifier, and 0.4g of toughening layer initiator.

[0140] The crushing strength, saturated exchange capacity and exchange rate of the ion exchange resins obtained in Examples 2 to 18 were tested.

[0141] Table 4. Crushing strength, saturated exchange capacity, and exchange rate test table of Examples 2 to 18

[0142] Crushing strength N / particle Saturated exchange capacity mmol / g Exchange rate mmol / (g·h) Example 2 9.5 2.62 1.07 Example 3 9.7 2.76 1.1 Example 4 9.9 2.7 1.12 Example 5 9.2 2.64 1.12 Example 6 10.3 2.84 1.16 Example 7 10.2 2.77 1.14 Example 8 9.8 2.8 1.14 Example 9 9.9 2.79 1.15 Example 10 9.8 2.78 1.1 Embodiment 11 10 2.8 1.14 Example 12 10.2 2.84 1.08 Example 13 10.3 2.86 1 Embodiment 14 8.5 2.43 1.15 Embodiment 15 9.1 2.62 1.13 Example 16 10.2 2.66 0.95 Embodiment 17 9.4 2.7 1.13 Embodiment 18 9.9 2.74 0.99

[0143] The present application studies the particle size of the zeolite powder added to the toughening layer in Examples 1 to 5.

[0144] The particle size of zeolite powder affects its distribution in the toughening layer and the average ion passage rate of the toughening layer composed of the resin part. Under the same mass dosage, the smaller the zeolite powder particle size, the more uniform the zeolite powder is dispersed in the toughening layer, and the better the ion redistribution effect is. From the perspective of ion redistribution, it has a favorable effect on the saturated exchange capacity of the ion exchange resin. However, the smaller the zeolite powder particle size, the more obvious the effect of reducing the ion passage rate of the resin part, which in turn has an adverse effect on the saturated exchange capacity of the ion exchange resin.

[0145] Combining Table 1 and Table 4, it can be seen from the experimental verification that the particle size of the zeolite powder in Examples 1 to 5 increases one by one, the influence of the zeolite powder on the ion passage rate of the toughening layer resin part gradually decreases, the exchange rate keeps increasing gradually, and the saturated exchange capacity reaches a peak in Example 3, and decreases significantly when comparing Example 4 with Example 5.

[0146] In combination with the crushing strength of Examples 1 to 5, the particle size of the zeolite powder in the toughening layer of the present application is preferably selected to be 10 to 13 μm.

[0147] The present application studies the pre-modification of zeolite powder added to the toughening layer in Examples 6 to 13.

[0148] On the basis of the preferred examples 3 and 4 of Examples 1 to 5, the zeolite powder was modified with the same silane coupling agent γ-glycidyloxypropyltrimethoxysilane to obtain the corresponding ion exchange resins - Examples 6 and 7.

[0149] Among them, Example 6 corresponds to Example 3, and Example 7 corresponds to Example 4. After modification with the silane coupling agent, the compatibility of the zeolite powder and the organic phase is improved, making the zeolite powder suspension easier to prepare, and the suspension time of the zeolite powder is longer and the suspension state is more stable, reducing the difficulty of molding the toughening layer and making the zeolite powder more evenly dispersed in the toughening layer. The toughening layer has better reinforcement effect, ion redistribution, and high concentration resistance on the ion exchange resin. All aspects of performance of Examples 6~7 are better than those of the corresponding Examples 3~4, and it is observed that the optimization improvement of Example 6 is higher than that of Example 7.

[0150] Examples 8-9, based on Example 6, studied the enhancement effects of other silane coupling agents, n-octyltrimethoxysilane and anilinemethyltriethoxysilane.

[0151] According to the results of Example 3, Example 6, Example 8, and Example 9 in Table 2 and Table 4, the performance of Example 6, Example 8, and Example 9 is better than that of Example 3, and among Example 6, Example 8, and Example 9, Example 6 remains the best. Therefore, the modification of n-octyltrimethoxysilane and anilinemethyltriethoxysilane can also achieve a similar improvement effect as that of γ-glycidyloxypropyltrimethoxysilane, but the modification effect of γ-glycidyloxypropyltrimethoxysilane is the best.

[0152] Because the silane coupling agent will affect the ion channels in the zeolite powder while improving the compatibility between the zeolite powder and the organic phase, as the amount of silane coupling agent compared to the zeolite powder increases, the more silane is grafted on the surface of the zeolite powder. After reaching a certain threshold, the ion channels on the surface of the zeolite powder will be affected by the steric hindrance of the grafted silane, and the ion passage rate will decrease; when the decrease is small, it will have a synergistic effect on the toughening layer's resistance to high-concentration ions, but this range is very small. When the decrease is large, it will affect the normal operation of the ions entering the core through the ion channels of the zeolite powder, affecting the overall exchange rate of the ion exchange resin. In Examples 10 to 13, this application studies the effect of the modified amount of silane coupling agent based on Example 6.

[0153] According to Table 2 and Table 4, the mass ratio of the modified amount of silane coupling agent in Example 10, Example 11, Example 6, Example 12, and Example 13 increases one by one.

[0154] As the mass ratio of the modified amount of silane coupling agent increases, the crushing strength continues to increase;

[0155] As the mass ratio of the modified amount of silane coupling agent increases, the saturated exchange capacity continues to increase, but the increasing trend has been significantly weakened between Example 6, Example 12, and Example 13;

[0156] As the mass ratio of the modified amount of silane coupling agent increases, the exchange rate reaches a peak value in Example 6, and decreases in Examples 12 and 13;

[0157] Therefore, when the mass ratio of the silane coupling agent to the zeolite powder is (0.05~0.08):1, the modified zeolite powder has good compatibility with the organic phase, and the silane coupling agent has little effect on the ion migration channel in the zeolite powder, and the effect is better.

[0158] This application studies the influence of the toughening layer thickness on the proportion of the ion exchange resin equivalent particle size using Examples 1 and 14 to 16, and controls the thickness of the toughening layer using the same zeolite powder but different amounts of secondary polymerization raw material liquid.

[0159] The thickness of the toughening layer of Example 14, Example 1, Example 15, and Example 16 is continuously increased, and the crushing strength and saturated exchange capacity of the ion exchange resin show an upward trend within this range, but there is a significant decrease in the exchange rate between Example 15 and Example 16. This is because as the proportion of the toughening layer thickness increases, the crushing strength of the ion exchange resin increases, but after the toughening layer thickness increases to a certain threshold, the exchange saturation rate of the ion exchange resin decreases significantly. This is because the toughening layer thickness is too large, and the outer thickening layer has completed the path redistribution of the ion exchange. The evenly distributed ions still need to move in the inner toughening layer with a slower migration speed, resulting in a decrease in the exchange saturation rate.

[0160] Therefore, the thickness of the toughening layer in the present application is preferably 9-11% of the resin equivalent diameter.

[0161] This application studies the effect of the dosage ratio of zeolite powder in the toughening layer on the ion exchange resin by using Examples 1 and 17-18.

[0162] In Example 17, the amount of zeolite powder in the secondary polymerization raw material liquid is 20g, which is less than 25g in Example 1; in Example 18, the amount of zeolite powder in the secondary polymerization raw material liquid is 30g, which is more than 25g in Example 1; the crushing strength of Examples 17, 1, and 18 gradually increases, and Example 1 is the best in saturated exchange capacity and exchange rate. The reason is that the particle size of zeolite powder has similar effects on ion exchange resin, and the zeolite powder in the toughening layer has multiple effects on ion redistribution and zeolite powder on resin ion channels. The larger the proportion of zeolite powder, the better the ion redistribution effect, but the more obvious the effect on reducing the speed of ions passing through the resin is. At the zeolite powder dosage ratio of Example 1, a better balance effect is achieved.

[0163] The process for recovering nickel sulfate from wastewater uses the ion exchange resins of Examples 1 to 18 of the present application, and the corresponding usage relationships are as follows.

[0164] Ion exchange resin source Embodiment 19 Example 1 Embodiment 20 Example 2 Embodiment 21 Example 3 Embodiment 22 Example 4 Embodiment 23 Example 5 Embodiment 24 Example 6 Embodiment 25 Example 7 Embodiment 26 Example 8 Embodiment 27 Example 9 Embodiment 28 Example 10 Embodiment 29 Embodiment 11 Embodiment 30 Example 12 Embodiment 31 Example 13 Embodiment 32 Embodiment 14 Embodiment 33 Embodiment 15 Embodiment 34 Example 16 Embodiment 35 Embodiment 17 Embodiment 36 Embodiment 18

[0165] By using the ion exchange resin of the present application, nickel can be recovered from wastewater in a long-term and stable manner, and has a good recovery efficiency for wastewater with large concentration fluctuations.

[0166] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. An ion exchange resin for recovering nickel from wastewater, characterized in that: The resin equivalent diameter is 2~3mm, with a core-shell structure, including a core, a toughening layer, and a shell layer from the inside to the outside. The core material is a porous polystyrene resin; The toughening layer is a composite of zeolite powder, polystyrene resin and binder, and the mass ratio of zeolite powder, polystyrene resin and binder in the raw materials of the toughening layer is (22-27):100:12; The shell layer is a porous polystyrene resin.

2. An ion exchange resin for recovering nickel from wastewater according to claim 1, characterized in that: The thickness of the toughening layer accounts for 9-11% of the resin equivalent diameter, and the particle size of the zeolite powder is 0.32-0.44% of the resin equivalent diameter.

3. An ion exchange resin for recovering nickel from wastewater according to claim 1, characterized in that: The zeolite powder is modified by a silane coupling agent, and the modification method is as follows: placing zeolite powder in an organic solution and dispersing it ultrasonically to obtain a zeolite powder suspension; Add γ-glycidyloxypropyltrimethoxysilane to the zeolite powder suspension, stir evenly, centrifuge and dry to obtain modified zeolite powder.

4. An ion exchange resin for recovering nickel from wastewater according to claim 3, characterized in that: The particle size of the zeolite powder is 9-11 μm.

5. The ion exchange resin for recovering nickel from wastewater according to claim 3, characterized in that: The mass ratio of the silane coupling agent to the zeolite powder is (0.05-0.08):

1.

6. The ion exchange resin for recovering nickel from wastewater according to claim 1, characterized in that: The binder is polymethacrylic acid.

7. A process for recovering nickel from wastewater, characterized in that: Use the ion exchange resin for nickel recovery from wastewater according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Nickel-containing wastewater recycling device and method

    CN111233209A

  • Production method of Al-Mg hydrotalcite composite polystyrene multi-component copolymerization ion exchange resin

    CN106238011A

  • Production method of polystyrene multi-copolyamide ion-exchange resin compounded from zeolite molecular sieve

    CN106279487A